Vibrational analysis of the ubiquitous interstellar molecule cyclopropenylidene (c-C3H2): the importance of numerical stability. (2nd January 2020) - Morgan, W. James; Fortenberry, Ryan C.; Schaefer III, Henry F.; Lee, Timothy J.
Abstract : Recent work on cyclopropenylidene, c -C 3 H 2, sought to improve on past ab initio results with a complete basis set (CBS) quartic force field method capable of predicting fundamental bands to within 5 cm −1 accuracy of gas-phase spectroscopy experiments for semirigid molecules. It was suggested that a problematic coupling between n -body correlation and 1-particle basis set effects prevented a proper application of this method for the out-of-plane bending vibrations of c -C 3 H 2 . We establish here that the actual source of this anomalous behaviour is numerical instability in the out-of-plane bending quartic force constants. It is found that the use of the normal equations to solve for the quartic force field, as well as a bending coordinate grid which is too compact, leads to errors of ca. 20 cm −1 in ν 5 and ν 9 . Our revised analysis shows ν 5 and ν 9 to be 980 cm −1 and 777 cm −1, respectively. GRAPHICAL ABSTRACT: